Utilization of and Relationships With Primary Care Providers During the Transition to Medicaid Managed Care. (September 2020) - Owen, Randall; Crabb, Caitlin; Stober, Kaitlin; Mitchell, Dale; Yamaki, Kiyoshi; Heller, Tamar
The objective of this study was to determine whether seniors and disabled adults in Illinois's Medicaid managed care (MMC) were more likely to see, maintain longitudinal relationships with, and have continuity of care with a primary care provider (PCP) compared with fee-for-service (FFS) Medicaid enrollees. Medicaid PCP service claims for 13, 221 MMC and 54, 625 FFS enrollees were analyzed using an inverse propensity score weighted difference-in-differences design to match the groups by demographic characteristics and historical Medicaid utilization. All data came from Medicaid claims data and corresponding administrative records. Regression analyses showed that enrollment in MMC was significantly related to each of the three outcomes; MMC enrollees were more likely than the FFS group to see a PCP during the 1-year post-period and have high levels of continuity of care with a single PCP. However, FFS enrollees were more likely to maintain a relationship with their PCP providers from the pre-period through the post-period. Therefore, while more people in MMC than FFS visit a PCP each year, for people in MMC, it is often a new provider relationship, which can be problematic for people with disabilities. Additional training for PCPs, to prepare them for working with people with disabilities, and additional efforts to expand the MMC network of providers are needed.